Chronologically constrained composite curves for carbon constrained agricultural planning - Wong, Wai Hong (Animo Repository, 2011)
The paper presents a generic model for the emission and repayment of carbon debt for the agricultural sector. Clearing of pristine land for food and energy crops is a major contribution to the rise in carbon emission especially in developing countries. It releases carbon stocks in vegetation as well as those trapped underground, and it typically takes years to repay the resulting carbon debt. This paper attempts to utilize composite curves to construct a graphical representation of carbon dioxide (CO2) levels over a finite time period. The aim is to produce a plantation scheduling system based on CO2 emission and manipulate the sizes of the land plots to meet the emission limit for the planning horizon. The final aim is to ultimately achieve an overall net reduction in CO2 level. © 2011 Elsevier Ltd.